Diversity And The Effect Of Water Quality And Barrier On Fish Community At Sungai Gombak - Halim, Nurul Fatinizzati Abd (2020)
Assessment on the fish assemblages in Sg. Gombak has been conducted to determine the current pattern of fish assemblages and is compared with previous data from Bishop (1973), Zakaria-Ismail (1994), and Aidah (1997). Besides, the study also had determined some factors affecting the pattern of fish distribution along Sg. Gombak (i.e. physicochemical water parameter and physical barrier). Fourteen sampling stations along the Sg. Gombak was determined and was separated into three zones (Upper, Middle, and Lower zones) as was exactly followed Bishop’s (1973) stations. Fish sampling at each station was repeated three times in the six-month sampling periods from February-August 2017 and using appropriate fishing gears (i.e. a backpack electro-shocker, scoop net, and cast net). Data analysis for the effect of the physical barrier (waterfall) was included with secondary data from Aidah’s (1997) and Bishop’s (1973) studies. In order to study the relationship between the environmental variables and longitudinal pattern of fish distribution, parameters of dissolved oxygen (DO) concentration (mg/L), temperature (°C), pН, and conductivity (μmho/cm) were measured in situ each time before fish sampling activities. In this study, 17 species from 11 families were recorded in Sg. Gombak. Most of the native fishes found in this study were distributed from Middle to Upper Zones, while the Lower Zone was dominated by the introduced species.